Carbamothioic S-acid derivative and kigamicins, the activated production of silent metabolites in Amycolatopsis alba DSM 44262Δabm9 elicited by N-acetyl-D-glucosamine. Issue 24 (16th December 2020) - Li, Xiaomei; Li, Xiaoman; Zhu, Jing; Wang, Haoxin; Lu, Chunhua
Abstract: One new carbamothioic S-acid derivative (1 ) and five known kigamicin derivatives (2 –6 ) were isolated from the fermentation extract of Amycolatopsis alba DSM 44262Δ abm9 elicited by N -acetyl-D-glucosamine. HPLC-DAD-UV analyses indicated that the DSM 44262Δ abm9 strain did not produce these metabolites originally and the production of 1 –6 was induced by adding 25 mM N -acetyl-D-glucosamine in the culture medium. The structures of 1 –6 were identified on the basis of NMR spectroscopic data and high-resolution ESIMS. These results highlight that addition of N -acetyl-D-glucosamine in the microbial culture medium could activate cryptic gene expression, induce and increase the production of new or known secondary metabolites. Graphical Abstract: